Temporomandibular Point and Its 2D and 3D Models - P. Hliňáková; T. Dostálová; J. Daněk; J. Nedoma (Czech Dental Chamber, 2008)
The aim of study is creating the two dimensional plain modeling of temporomandibular point. Three different pressures and movements are evaluated.